Traumatic experiences and place of occurrence: An analysis of sex differences among a sample of recently arrived immigrant adults from Latin America. - Laura X Vargas; Mary D Sammel; Therese S Richmond; Connie M Ulrich; Zachary D Giano; Lily Berkowitz; C Neill Epperson (PLoS ONE)
With increasing violence, political, and economic instability in Latin America, there is a record number of migrants crossing the U.S. southern border. Latin American migrants are often exposed to traumatic events before leaving their home country and during migration. While prior studies document that sex may play a role in types of traumatic exposure, few studies compare differences in traumatic exposure by sex and place of occurrence of recently arrived immigrants. Addressing this gap, we recruited 120 adults who had recently crossed the U.S.-Mexico border. Participants completed questionnaires to characterize trauma exposures in their home country and during their migration journey. Results found that men reported higher levels of exposure to combat situations, while women were more likely to experience sexual assault. Both combat exposure and sexual traumas occurred more often in home countries than during migration. More than half of the full sample reported being threatened with a firearm. These data confirm gender differences in type of trauma and that exposures in the country of origin may provide the impetus to migrate.